Probing skin physiology through the volatile footprint: Discriminating volatile emissions before and after acute barrier disruption. Issue 10 (3rd July 2017) - Duffy, Emer; Jacobs, Matthew R.; Kirby, Brian; Morrin, Aoife
Abstract: Volatile organic compounds emitted by human skin were sampled before and after acute barrier disruption of the volar forearm to investigate the significance of this approach to skin physiology research. A small wearable housing integrating a solid‐phase micro‐extraction fibre permitting rapid enclosed headspace sampling of human skin volatiles is presented, enabling non‐invasive sample collection in 15 minutes, in a comfortable wearable format. Gas chromatography‐mass spectrometry was utilised to separate and identify the volatile metabolites. A total of 37 compounds were identified, with aldehydes (hexanal, nonanal, decanal), acids (nonanoic, decanoic, dodecanoic, tetradecanoic and pentadecanoic acids) and hydrocarbons (squalane, squalene) predominant within the chemical profile. Acute barrier disruption was achieved through tape stripping (TS) of the stratum corneum to determine the impact on the volatile signature. Principle component analysis demonstrated there to be a discriminating volatile signature before and after TS. The dysregulation of significant features was examined. Several compounds derived from sebaceous components and their oxidation products were altered following barrier disruption, including squalane, squalene, octanal and nonanal. The upregulation of glycine was also observed, which may indicate a perturbation to the skin's natural moisturising factor production. TS impacted the hydro‐lipid film that functions within the skin barrier, resulting in a differing volatile signature from affected skin. This provides a valuable non‐invasive approach for scientific and clinical studies in dermatology, particularly around dermatological disorders associated with compromised barrier function.